2008
DOI: 10.1055/s-2008-1075038
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Oxygen and Head Growth in Infants with Bronchopulmonary Dysplasia

Abstract: Infants with bronchopulmonary dysplasia (BPD) are known to have developmental delays, but a direct link between oxygen (O (2)) exposure and brain growth has not been explored. Our objective was to test the hypothesis that the use of O (2) is associated with delays in head growth (DHG) in premature infants with BPD. We conducted a retrospective study on a cohort of infants with BPD (birthweight [BW] < 1500 g, gestational age < 34 weeks). The study population was divided into two groups based on their head circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…While attempts have been made to limit the dose and duration of exposure of supplemental oxygen to the immature lungs [29]–[32], given the decreased capacity of the preterm infants to combat oxidative stress, it is not surprising that supplemental oxygen that is required for prolonged periods in this population results in significant medical consequences. The duration of exposure to supplemental oxygen has been associated with delayed head growth [33], and need for supplemental oxygen at 36 weeks PMA has been associated with significant neurodevelopmental delays at 12–24 months CA [34][37]. In contrast, a recent study has noted that BPD accompanied by invasive mechanical ventilation at 36 weeks PMA strongly predicted the more common bilateral CP phenotypes (assessed at 2 years), but BPD without invasive mechanical ventilation (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…While attempts have been made to limit the dose and duration of exposure of supplemental oxygen to the immature lungs [29]–[32], given the decreased capacity of the preterm infants to combat oxidative stress, it is not surprising that supplemental oxygen that is required for prolonged periods in this population results in significant medical consequences. The duration of exposure to supplemental oxygen has been associated with delayed head growth [33], and need for supplemental oxygen at 36 weeks PMA has been associated with significant neurodevelopmental delays at 12–24 months CA [34][37]. In contrast, a recent study has noted that BPD accompanied by invasive mechanical ventilation at 36 weeks PMA strongly predicted the more common bilateral CP phenotypes (assessed at 2 years), but BPD without invasive mechanical ventilation (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Head circumference is often utilized as an indirect measure of postnatal brain growth, and the literature has shown an association between suboptimal brain growth and subsequent neurodevelopmental impairment (22)(23)(24). Nesterenko, et al demonstrated a correlation between oxygen exposure and delays in head growth at six months corrected age in infants with moderate to severe BPD with birth head circumference less than the 50th percentile (25). However, it remains to be determined whether the oxygen exposure is directly related to the pathogenesis of delayed head growth or is simply a marker of clinical illness severity.…”
Section: Discussionmentioning
confidence: 99%